2010
DOI: 10.1007/s11250-010-9568-4
|View full text |Cite
|
Sign up to set email alerts
|

Response of Ross 308 and Hubbard broiler chickens to feed removal for different durations during the day

Abstract: The effects of feed removal for 6, 8, or 10 h during the day from 8 to 28 days of age followed by ad libitum feeding to market age on the growth performance of two strains of broiler chickens, Ross 308 and Hubbard, were studied over 7 weeks. Ross 308 was superior to Hubbard in weight gain and final body weight but consumed more feed and deposited more abdominal fat. Overall, daily feed removal reduced feed intake and improved feed efficiency in all feed-restricted birds, and the longer the period of feed remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
6
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
7
6
2
Order By: Relevance
“…The significant differences between the strains in feed efficiency and mortality rate are contrary to reports of insignificant differences by Dozier et al (2003) and Benyi et al (2009). The significant strain difference in abdominal fat in this study supports a similar observation by Santos et al (2005) and Benyi et al (2010). A positive genetic correlation ranging from 0.21 to 0.36 exists between live weight and abdominal fat percentage (Chambers 1990).…”
Section: Discussionsupporting
confidence: 73%
“…The significant differences between the strains in feed efficiency and mortality rate are contrary to reports of insignificant differences by Dozier et al (2003) and Benyi et al (2009). The significant strain difference in abdominal fat in this study supports a similar observation by Santos et al (2005) and Benyi et al (2010). A positive genetic correlation ranging from 0.21 to 0.36 exists between live weight and abdominal fat percentage (Chambers 1990).…”
Section: Discussionsupporting
confidence: 73%
“…A number of variations of feed restriction including limiting the time of daily access to feed (Khetani et al, 2009;Onbasilar et al, 2009;Mohebodini et al, 2009), removal of feed for up to 8 h a d or skip-a-day feeding, allowing birds to feed only once/h and feeding once every other day (Demir et al, 2004;Khajali et al, 2007;El-Fiky et al, 2008;Benyi et al, 2009Benyi et al, , 2010Boostani et al, 2010;Saffar & Khajali, 2010), have been evaluated but results have been conflicting (Navidshad et al, 2006;Cornejo et al, 2007;Khetani et al, 2009;Ghazanfari et al, 2010). However, Mohebodini et al (2009) on the respective research indicated that although intermittent feeding through free access to feed during four periods of 2 h (06:00-08:00, 12:00-14:00, 18:00-20:00, and 24:00-02:00) from 7-21 d of age had lower on body weight gain than control (436.3 vs 495.3 g), but had no effect on weight gain during realimentation period from 22-42 d of age.…”
Section: Introductionmentioning
confidence: 99%
“…Feed restriction is a management strategy, which is applied in the poultry industry in order to reduce the feed intake, to limit the early growth, to decrease the incidence of infectious, metabolic and skeletal disorders and to improve the nutrient utilization via compensatory growth (Zulkifli et al, 1993;Zhan et al, 2007;Thompson et al, 2008;Benyi et al, 2010). In the present study, the reduction in body weight as well as the change of feed conversion ratio in experimental groups where feed restriction was applied, is in agreement with the results of the study of Lee & Leeson (2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several qualitative and quantitative feed restriction programmes have been tried in attempts to reduce the feed intake, limit the early growth and decrease the incidence of infectious, metabolic and skeletal disorders (Zulkifli et al, 1993;Zhan et al, 2007;Thompson et al, 2008;Benyi et al, 2010). The main target of feed restriction is to reduce the nutrients in the gastrointestinal tract, so that they can be utilized by neither birds nor intestinal microbiota (Tsiouris, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation